The Expression of STAT3, BCL-XL and MMP-2 Proteins in Colon Adenocarcinomas and their Relationship with Prognostic Factors - Artas, Gokhan; Ozercan, H. Ibrahim (Federation Turkish Pathology Soc, 2014)
Objective: Colon adenocarcinomas are the most common malignancy of the gastrointestinal tract. Many factors are described in the prognosis. Herein we aimed to determine the relationship between signal transducer and activator of transcription 3(STAT3), B-cell lymphoma-extra large (Bcl-xL) and matrix metalloproteinase-2 (MMP-2) expression in colon adenocarcinomas and their relationship with prognostic factors. Material and Method: A total of 45 colon adenocarcinomas (15 well, 15 moderately, 15 poorly differentiated) and 15 normal colon mucosa samples were selected randomly. The STAT3, Bcl-xL and MMP-2 immunohistochemicals were applied to the samples. Results: There was a significant difference between the normal mucosa and carcinoma group regarding the STAT3 staining diffuseness and intensity (p<0.05), but not for Bcl-xL (p>0.05). The intensity of MMP-2 significantly differed between the normal mucosa and the carcinoma group (p<0.05). The diffuseness of STAT3 and the intensity of MMP2 showed a significant association with the degree of differentiation (p<0.05). The intensity and diffuseness of BcL-xL did not show a relationship with the degree of differentiation (p>0.05). Evaluation of the diffuseness and intensity of the three markers with lymph node metastasis and tumor size revealed that only MMP2 diffuseness had a negative correlation with tumor size (r=-0.318). Conclusion: We observed that Bcl-xL does not have a role in the diagnosis of colon adenocarcinomas or the detection of the degree of differentiation, a prognostic factor, but such a relationship was observed for STAT3 and MMP-2.
Kolon adenokarsinomlari{dotless}nda STAT3, BCL-XL ve MMP-2 proteinlerinin sali{dotless}ni{dotless}mi{dotless}ni{dotless}n tani{dotless}sal de?eri ve prognostik faktörler ile İlişkisi
Keywords: Colonic neoplasms; STAT3 protein; Bcl-xL protein; Matrix Metalloproteinase 2; Prognosis